2023
DOI: 10.3390/agriculture13040901
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Agronomical Factors Limiting Differences in Potato Yielding between Organic and Conventional Production System

Abstract: This paper presents the results of the authors’ own research and literature research on the impact of selected environmental and agronomical factors on the yield of potato grown under the organic system and the possibility of increasing the yield. The results are based on research conducted for several years at the Institute of Plant Breeding and Acclimatization in Jadwisin, Poland. The influence of factors such as soil quality and climatic conditions, selection of varieties, seed potato preparation, irrigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…According to Priegnitz et al [39], increasing the number of stems from one potato plant can lead to higher seed potato yield because each stem has the potential to generate a greater number of tubers. Similar relationships are confirmed by the studies of Zarzyńska et al [37] and Barbaś and Sawicka [38].…”
Section: Correlations Between Potato Tuber Characteristicssupporting
confidence: 86%
See 1 more Smart Citation
“…According to Priegnitz et al [39], increasing the number of stems from one potato plant can lead to higher seed potato yield because each stem has the potential to generate a greater number of tubers. Similar relationships are confirmed by the studies of Zarzyńska et al [37] and Barbaś and Sawicka [38].…”
Section: Correlations Between Potato Tuber Characteristicssupporting
confidence: 86%
“…Some varieties may be more resistant to specific weather conditions than others; b) adaptation to local conditions: some varieties may be better adapted to specific climatic and soil conditions prevailing in a particular region. Varieties well suited to certain conditions may show better tuber yields compared to varieties less adapted to these conditions; c) genetic flexibility: some varieties may be more genetically flexible, meaning they can better respond to variable weather conditions by quickly adapting to changes in the environment; d) genotype-environment interactions: the variety's response to weather conditions may also result from interactions between genetic traits and environmental conditions, meaning that the influence of weather conditions on plants can be modified by their genotype [34,[36][37][38].…”
Section: Impact Of Environmental Conditions On Potato Yield and Its P...mentioning
confidence: 99%
“…Reviews by De Ponti et al [15] and Seufuret et al [16] concluded that organic arable yields average 80% and 75% of conventional production, respectively. Djaman et al [17] and Zarzy ńska et al [18] also report large differences in yield depending on the production system. However, the yield gap varies between crop species, with tuber crops having a greater yield gap than cereals.…”
Section: Introductionmentioning
confidence: 97%